Strategi Adaptasi Pelaku Usaha Wisata Selama Masa Pandemi Covid-19 - Minarti Manik; Agus Suriadi (JSSH (Jurnal Sains Sosial dan Humaniora), 2023)
Covid-19 pandemic as a deadly epidemic that has spread since 2020 has affected various aspects of human life. Various policies to prevent the spread of this epidemic have affected the activities of tourism business. The biggest impact is the decline in the income of businessmen, due to the drastic drop of tourist visits. Tourism businessmen have to find ways to cope and adapt themselves during this pandemic, and this method is called as adaptive strategy. This study aims to find out about businessmen’s strategies in Sidamanik Tea Garden tourist area to survive during the Pandemic. The method used is descriptive research wtih qualitative approach. The results of this study indicate that tourism businessmen apply several adaptive strategy, namely active strategy is done by working part-times, and involve the family members to increase the income. The passive strategy is done by implementing a frugal lifestyle, reducing the expenditures. The network strategy is done by lending money from relatives, and utilizing assistance programs by the government.